Development of the Human Breast - Javed, Asma; Lteif, Aida (Seminars in Plastic Surgery, 2013)
Mammalia are so named based on the presence of the mammary gland in the breast. The mammary gland is an epidermal appendage, derived from the apocrine glands. The human breast consists of the parenchyma and stroma, originating from ectodermal and mesodermal elements, respectively. Development of the human breast is distinctive for several reasons. The human breast houses the mammary gland that produces and delivers milk through development of an extensive tree-like network of branched ducts. It is also characterized by cellular plasticity, with extensive remodeling in adulthood, a factor that increases its susceptibility to carcinogenesis. Also, breast development occurs in distinct stages via complex epithelial–mesenchymal interactions, orchestrated by signaling pathways under the regulation of systemic hormones. Congenital and acquired disorders of the breast often have a basis in development, making its study essential to understanding breast pathology.
Keywords: breast embryology; mammary gland development; Tanner staging